Deleterious effects of lard-enriched diet on tissues fatty acids composition and hypothalamic insulin actions. (December 2015) - Dornellas, A.P.S.; Watanabe, R.L.H.; Pimentel, G.D.; Boldarine, V.T.; Nascimento, C.M.O.; Oyama, L.M.; Ghebremeskel, K.; Wang, Y.; Bueno, A.A.; Ribeiro, E.B.
Abstract: Altered tissue fatty acid (FA) composition may affect mechanisms involved in the control of energy homeostasis, including central insulin actions. In rats fed either standard chow or a lard-enriched chow (high in saturated/low in polyunsaturated FA, HS-LP) for eight weeks, we examined the FA composition of blood, hypothalamus, liver, and retroperitoneal, epididymal and mesenteric adipose tissues. Insulin-induced hypophagia and hypothalamic signaling were evaluated after intracerebroventricular insulin injection. HS-LP feeding increased saturated FA content in adipose tissues and serum while it decreased polyunsaturated FA content of adipose tissues, serum, and liver. Hypothalamic C20:5n-3 and C20:3n-6 contents increased while monounsaturated FA content decreased. HS-LP rats showed hyperglycemia, impaired insulin-induced hypophagia and hypothalamic insulin signaling. The results showed that, upon HS-LP feeding, peripheral tissues underwent potentially deleterious alterations in their FA composition, whist the hypothalamus was relatively preserved. However, hypothalamic insulin signaling and hypophagia were drastically impaired. These findings suggest that impairment of hypothalamic insulin actions by HS-LP feeding was not related to tissue FA composition.